If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x-(-7x-4x)=2x(3x+4)
We move all terms to the left:
-5x-(-7x-4x)-(2x(3x+4))=0
We add all the numbers together, and all the variables
-5x-(-11x)-(2x(3x+4))=0
We get rid of parentheses
-5x+11x-(2x(3x+4))=0
We calculate terms in parentheses: -(2x(3x+4)), so:We add all the numbers together, and all the variables
2x(3x+4)
We multiply parentheses
6x^2+8x
Back to the equation:
-(6x^2+8x)
6x-(6x^2+8x)=0
We get rid of parentheses
-6x^2+6x-8x=0
We add all the numbers together, and all the variables
-6x^2-2x=0
a = -6; b = -2; c = 0;
Δ = b2-4ac
Δ = -22-4·(-6)·0
Δ = 4
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{4}=2$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-2}{2*-6}=\frac{0}{-12} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+2}{2*-6}=\frac{4}{-12} =-1/3 $
| k-8/2=1 | | (7/3)x=10 | | 33-z=20z+12 | | 1.5(f-11)=12 | | -9.86+2d=-18.86 | | 1.4=m/4-2 | | 5(1+4m)=2(3+0m) | | g/4-4=-0.5 | | 20=4(p-13) | | 17=a/7-2 | | 26+x=x+23 | | 0=−1/5x^2−10 | | -4p-p=-5 | | g/3+7.9=10.9 | | y=−1/5^2−10 | | 14w+9=5(2w-3)+4w+24 | | 2(m+-2)=-6 | | b/2+4=6.59 | | -r+18=9 | | 9-3x+28=54 | | 2/9m−1/9=9/90 | | -4.3(c-20)=12.9 | | -1=3x-4x | | 20x+20=7x | | 1x=-14x | | 6(4a+1.5)=-3(-8a-3) | | 87=3(4v-3) | | r-2.2/3=1.3 | | 2t-9.74=2.26 | | -2.98=3m-7 | | -6u+2-6=-16 | | 8d-10d-6=-6-2d |